Immune checkpoint inhibitor-associated autoimmune encephalitis and other neurological immune-mediated adverse events: a pharmacovigilance study using the FAERS and JADER - Di, Xiaomeng; Shi, Xiaohong; Gai, Feng; Wang, Jiawei (Frontiers in Oncology, 2025)
BackgroundImmune checkpoint inhibitor (ICI)-associated neurological immune-related adverse events (NAEs) are rare but serious side effects, of which autoimmune encephalitis (AIE) is a potentially fatal central nervous system disorder requiring more attention.MethodsWe performed a retrospective disproportionality analysis of NAE reports in the FDA Adverse Event Reporting System (FAERS) and the Japanese Adverse Event Reporting Database (JADER) from 2004 to 2024, utilizing reporting odds ratio (ROR), proportional reporting ratio (PRR), the Bayesian confidence propagation neural network BCPNN, and the multi-item gamma Poisson shrinker (MGPS) for signal detection.ResultsIn total, 3,999 reports of ICI-associated NAEs were identified from the FAERS database, of which 1,998 reports were AIE. 1,558,251 reports of AEs were collected from the JADER database, which contained 890 AIE reports. ICIs, including pembrolizumab, nivolumab, atezolizumab, ipilimumab, and durvalumab, were identified among the top 30 agents in both databases, demonstrating significant signals across all 4 algorithms. Except for noninfectious myelitis, acute disseminated encephalomyelitis, and multiple sclerosis, positive signals were detected in all other preferred terms (PTs). These NAEs accounted for 23.7% of total mortality, with myasthenia gravis (MG) exhibiting the highest mortality rate at 30.63%. Specific PTs, such as aseptic meningitis, AIE, chronic inflammatory demyelinating polyradiculoneuropathy, Guillain-Barré syndrome, MG, myelitis, and immune-related myopathy, were associated with the severity of outcomes, showing significant statistical differences between severe and non-severe cases (p < 0.05).ConclusionOur study found a notable correlation between ICIs and AIE and other specific NAEs, highlighting the demographic characteristics, time to onset, and disease severity of ICI-induced NAEs, thereby facilitating the timely recognition and treatment of these ICI therapy-related complications.